KONSTRUKSI HUKUM PROGRESIF; URGENSINYA DALAM PENYELESAIAN SENGKETA EKONOMI SYARI’AH - Salasti Faridatun Hasanah; A. Kumedi Ja’far; M. Iqbal Fasa (EKSYA : Jurnal Ekonomi Syariah, 2021)
Dutch colonialism made Indonesia embrace the legal positivism system. Legal positivism views the law as a a fixed, logical and closed system. The written law is so exalted and does not allow contextual interpretation. The truth that is believed is the truth that can be proven (pragmatic). Along with the development of the era, which is marked by the increasingly complex problems that arise, including sharia economics, it cannot be solved with a positivistic paradigm. The law must develop along with the development of problems in society in order to create the ideals of justice. with similar thought, satjipto rahardjo then sparked his progressive legal concept which places humans and humanity as the main discourse or primus in the discussion and enforcement of law and formulated an adagium "law is for human, not human for law". The progressive law that place "law for humans" and "substantive justice" are in line with the goals of as-Shari'a in creating law, namely for the maslahah. Thus, the use of a progressive legal paradigm in resolving sharia economic disputes is appropriate. The urgency of progressive law itself in resolving sharia economic disputes, including: as a new paradigm of legal discovery, reconstructing the role of judges who are passive to active, and supporting mediation as an alternative dispute resolution in sharia economic disputes.